Intuition in Managerial Decision-Making - CONSTANTINESCU, Pompiliu; CONSTANTINESCU, Mădălina (Journal of Advanced Research in Management, 2018)
Through the research into intuition and its role in managerial decision-making we are going to try and lay emphasis on the situations when people gain understanding of what intuition is and how to use is successfully. In order to do so, we are going to summarize a variety of researches into the realm of intuition and emphasize several theoretical recommendations. While this revision helps us take into consideration several disputes regarding intuition, it also arises some problems and focuses on new opportunities of study. Another relevant aspect of our carryout presents the most acute controversies - from our own perspective – in the study of intuition.